High Diversity of Human Non-Polio Enterovirus Serotypes Identified in Contaminated Water in Nigeria - Majumdar, Manasi (Viruses, 2021)
Human enteroviruses (EVs) are highly prevalent in sewage and have been associated with human diseases with complications leading to severe neurological syndromes. We have used a recently developed molecular method to investigate the presence of EVs in eight samples collected in 2017–2018 from water streams contaminated by drainage channels in three different locations in Nigeria. A total of 93 human EV strains belonging to 45 different serotypes were identified, far exceeding the number of strains and serotypes found in similar samples in previous studies. Next generation sequencing analysis retrieved whole-capsid genomic nucleotide sequences of EV strains belonging to all four A, B, C, and D species. Our results further demonstrate the value of environmental surveillance for the detection of EV transmission of both serotypes commonly associated with clinical syndromes, such as EV-A71, and those that appear to circulate silently but could eventually cause outbreaks and disease. Several uncommon serotypes, rarely reported elsewhere, were detected such as EV-A119, EV-B87, EV-C116, and EV-D111. Ten EV serotypes were detected in Nigeria for the first time and two of them, CV-A12 and EV-B86, firstly described in Africa. This method can be expanded to generate whole-genome EV sequences as we show here for one EV-D111 strain. Our data revealed phylogenetic relationships of Nigerian sewage strains with EV strains reported elsewhere, mostly from African origin, and provided new insights into the whole-genome structure of emerging serotype EV-D111 and recombination events among EV-D serotypes.